Parkett : The Parkett series with contemporary artists. (Zürich : Parkett-Verlag, 1993)
Table of Content : The Aesthetic Illusion by Jean Baudrillard ; Charles Ray Ray’s Tack by Peter Schjeldahl ; All For One and One For All by Robert Storr ; Some Bodes by Klaus Kertess ; Charles Ray’s Still Lives by Christopher Knight ; Franz West The Soul is the Body’s Envelope by Denys Zacharopoulos ; Pelop’s Meal by Elisabeth Schlebrügge ; Conversation by Harald Szeemann ; Sex in the Afternoon by Jan Avgikos ; Collaboration and the Issue of Completion by Martin Prinzhorn ; 3 or 17 by Franz West & Axel Huber ; Pipilotti Rist, Insert Silent Music: Luc Tuymans by Hans Rudolf Reust ; Inquiry: Cherchez la femme peintre! Privat, Cumulus from Europe by Gertrud Sandqvist ; To Dream the Dangers We Are Entertaining, Cumulus from Europe by Gary Michael Dault
As painters, Ross Bleckner and Marlene Dumas share a concentration on lightness and darkness in their quest for the essence of light. Their semantic spectrum ranges from the color of the skin to metaphysical implications. People are central to the oeuvres of both artists: They figure concretely in the paintings of Marlene Dumas, while in Ross Bleekner’s works, they acquire a presence of great urgency through the very fact of their absence. An acutely heightened perception of reality serves as the point of departure for both artists, resulting in painting that is a network of relations between motif and material. Moreover, they both draw on the medium of photography: Marlene Dumas paints from photographs, while Ross Bleckner’s black-and-white photographs were taken especially for this issue of Parkett. In the photographic Insert, Rudi Molacek has sought out the eye of the animal to record the relationship established at the moment of contact. In the impression of a calendar, the photographs serve as visual mottos for past and future months. (editorial by publisher)
boek
Keywords: Bleckner, Ross; Dumas, Marlene